Are Distal and Proximal Visual Cues Equally Important during Spatial Learning in Mice? A Pilot Study of Overshadowing in the Spatial Domain - Hébert, Marie; Bulla, Jan; Vivien, Denis; Agin, Véronique (Frontiers in Behavioral Neuroscience, 2017)
Animals use distal and proximal visual cues to accurately navigate in their environment, with the possibility of the occurrence of associative mechanisms such as cue competition as previously reported in honey-bees, rats, birds and humans. In this pilot study, we investigated one of the most common forms of cue competition, namely the overshadowing effect, between visual landmarks during spatial learning in mice. To this end, C57BL/6J x Sv129 mice were given a two-trial place recognition task in a T-maze, based on a novelty free-choice exploration paradigm previously developed to study spatial memory in rodents. As this procedure implies the use of different aspects of the environment to navigate (viz., mice can perceive from each arm of the maze) we manipulated the distal and proximal visual landmarks during both the acquisition and retrieval phases. Our prospective findings provide a first set of clues in favor of the occurrence of an overshadowing between visual cues during a spatial learning task in mice when both types of cues are of the same modality but at varying distances from the goal. In addition, the observed overshadowing seems to be non-reciprocal, as distal visual cues tend to overshadow the proximal ones when competition occurs, but not vice versa. The results of the present study offer a first insight about the occurrence of associative mechanisms during spatial learning in mice, and may open the way to promising new investigations in this area of research. Furthermore, the methodology used in this study brings a new, useful and easy-to-use tool for the investigation of perceptive, cognitive and / or attentional deficits in rodents.